College Athletes' Rights in the Age of the Super Conference - Ellen Staurowsky (University of Kansas Libraries, 2014)
Among the most central ethical obligations that higher education in the United States owes to students is the protection of their right to freely disagree, form judgments on their own, and evaluate evidence (AAC&U Board of Directors, 2006). This commentary argues that the ethical obligation to ensure that the academic freedom that should be available to all students is not met when it comes to the treatment of college athletes, most particularly those college athletes participating in the big-time, revenue-generating sports of football and men's basketball. Using the case example of the All Players United (APU) Campaign, a protest staged by less than two dozen college football players in the fall of 2013, issues associated with athletes right to freedom of speech and freedom of association are examined. The All Players United (APU) campaign is first described followed by an exploration of the group think evidenced in the reaction by college sport officials and football coaches to the APU. To provide context, the APU action is considered within a broader historical overview of college athlete protests and attempts to affect change in the areas of compensation, health and well-being, and educational access. Using a conceptual frame that recognizes that college athletes are recognized as neither workers nor students, difficulties associated with the location of college athletes' rights are explored. This commentary concludes with final thoughts regarding the implications of limiting avenues for athlete self-advocacy within higher education in light of efforts by the Northwestern football team to be recognized as employees with the right to unionize and collectively bargain.